Genomic selection signatures in farmed Colossoma macropomum from tropical and subtropical regions in South America - Agudelo, John Fredy Gómez [UNESP]; Mastrochirico-Filho, Vito Antonio [UNESP]; Borges, Carolina Heloisa de Souza [UNESP]; Ariede, Raquel Belini [UNESP]; Lira, Lieschen Valeria Guerra [UNESP]; Neto, Rubens Ricardo de Oliveira [UNESP]; de Freitas, Milena Vieira [UNESP]; Sucerquia, Gustavo Adolfo Lenis; Vera, Manuel; Berrocal, Milthon Honorio Muñoz; Hashimoto, Diogo Teruo [UNESP] (Wiley, 2022)
Tambaqui or cachama (Colossoma macropomum) is one of the most important neotropical freshwater fish used for aquaculture in South America, and its production is concentrated at low latitudes (close to the Equator, 0°), where the water temperature is warm. Therefore, understanding how selection shapes genetic variations and structure in farmed populations is of paramount importance in evolutionary biology. High-throughput sequencing to generate genome-wide data for fish species allows for elucidating the genomic basis of adaptation to local or farmed conditions and uncovering genes that control the phenotypes of interest. The present study aimed to detect genomic selection signatures and analyze the genetic variability in farmed populations of tambaqui in South America using single-nucleotide polymorphism (SNP) markers obtained with double-digest restriction site-associated DNA sequencing. Initially, 199 samples of tambaqui farmed populations from different locations (located in Brazil, Colombia, and Peru), a wild population (Amazon River, Brazil), and the base population of a breeding program (Aquaculture Center, CAUNESP, Jaboticabal, SP, Brazil) were genotyped. Observed and expected heterozygosity was 0.231–0.350 and 0.288–0.360, respectively. Significant genetic differentiation was observed using global FST analyses of SNP loci (FST = 0.064, p < 0.050). Farmed populations from Colombia and Peru that differentiated from the Brazilian populations formed distinct groups. Several regions, particularly those harboring the genes of significance to aquaculture, were identified to be under positive selection, suggesting local adaptation to stress under different farming conditions and management practices. Studies aimed at improving the knowledge of genomics of tambaqui farmed populations are essential for aquaculture to gain deeper insights into the evolutionary history of these fish and provide resources for the establishment of breeding programs.
Keywords: genetic structure; neotropical fish; serrasalmidae; signatures of selection; South American Aquaculture; stress in aquaculture